Efekt léčby kombinací trifluridin/tipiracilu s bevacizumabem - Batko, Stanislav; Pudil, Jiří (Onkologie, 2024)
The treatment of metastatic colorectal cancer involves a multimodal approach including systemic treatment with chemotherapy, targeted therapy or immunotherapy, and where possible surgical intervention or other local methods as well. In the third line and beyond, clinicians' expectations have tended to be modest, however advances in new treatment combinations have expanded our options and shown the possibility of persistent treatment responses. This case report demonstrates the case of a patient with a pre-treated disease where trifluridine/tipiracil with bevacizumab led to a durable response. Trifludine/tipiracil in third-line therapy represents an effective and well-tolerated option suitable for the vast majority of patients.
Keywords: Colorectal Neoplasms; pyrrolidiny; Bevacizumab; kombinovaná farmakoterapie; mužské pohlaví; trifluridin; Drug Combinations; Male; Liver Neoplasms; trifluridin/tipiracil; Humans; Antineoplastic Agents; lidé; metastázy nádorů; Middle Aged; lidé středního věku; bevacizumab; Adenocarcinoma; Pyrrolidines; Trifluridine; Drug Therapy, Combination; kolorektální nádory; Neoplasm Metastasis; protinádorové látky; adenokarcinom; nádory jater; fixní kombinace léků